2015
DOI: 10.1039/c5cy00665a
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient Ga/ZSM-5 catalyst prepared by formic acid impregnation and in situ treatment for propane aromatization

Abstract: A simple method for the preparation of a Ga/ZSM-5 catalyst for propane aromatization was established by formic acid impregnation and in-situ treatment. The catalyst prepared by this novel method showed remarkably superior activity of propane aromatization. Under the conditions: T = 540 °C, P = 100 kPa, WHSV = 6000 ml/(g·h) and with a N 2 /C 3 H 8 molar ratio of 2, the highest propane conversion and 10 selectivity of BTX (benzene, toluene and xylene) on H-Ga/SNSA catalyst achieved was 53.6% and 58.0% respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 52 publications
5
83
0
Order By: Relevance
“…This process is also used industrially to upgrade light alkanes such as ethane, propane and butane in the petroleum refinery. [6][7][8][9] ZSM-5 is known to be one of the best catalysts for the aromatization reaction mostly due to its controllable acidity, its high-temperature stability and its shape selectivity due to its pore structure. Most of the reported studies indicate that the yield of aromatics can be increased mainly by using a doping metal.…”
Section: Introductionmentioning
confidence: 99%
“…This process is also used industrially to upgrade light alkanes such as ethane, propane and butane in the petroleum refinery. [6][7][8][9] ZSM-5 is known to be one of the best catalysts for the aromatization reaction mostly due to its controllable acidity, its high-temperature stability and its shape selectivity due to its pore structure. Most of the reported studies indicate that the yield of aromatics can be increased mainly by using a doping metal.…”
Section: Introductionmentioning
confidence: 99%
“…Ausavaukhi et al [13] prepared a series of Ga-containing ZSM-5 zeolites via impregnation and physical mixing and determined that the GaO + species act as stronger Lewis acid sites. Xiao et al [14,15] also reported that the extraframework GaO + species in impregnated ZSM-5 samples can react with the acidic protons of the zeolite framework and contribute to a strong Lewis acidity, which is favorable for dehydrogenation during propane aromatization under a N 2 atmosphere. Rodrigues et al [16,17] studied the nature and activity of gallium species for the aromatization of propane under H 2 and concluded that the reduced gallium species, which were obtained via hydrogen reduction of GaO + species (GaH 2 + ), in the impregnated ZSM-5 zeolites serve as the actual active sites for propane activation.…”
Section: Introductionmentioning
confidence: 99%
“…Alkylation and disproportionation of toluene are another route to produce xylenes. So far, zeolite catalysts for BTX synthesis from C 1‐3 feedstocks like methanol (MeOH), dimethyl ether (DME), ethanol (EtOH), acetone and so on have been widely studied . However, separation of p ‐xylene from other isomers is a serious issue because the difference in boiling points between them is too small to separate them by distillation.…”
Section: Figurementioning
confidence: 99%